Sensory evaluation of tea with different brewing conditions: a systematic review of recent 10-year studies - I Gde Adi Suryawan Wangiyana; I Gusti Agung Ayu Hari Triandini (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The phytochemical profile of tea beverages under different brewing conditions should be further examined using sensory evaluation to measure preference levels, which are essential for product development. This study aims to comprehensively review the sensory profile of tea beverages with different adjustments to the brewing conditions from recent 10-year publications. This study used the methodological standards outlined in the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) across five databases (Scopus, Web of Science, ScienceDirect, ProQuest, and CABI). The Office of Health Assessment and Translation (OHAT) was used for risk bias assessment. A total of 1555 articles were identified, yielding 24 eligible studies. Various brewing conditions were identified in the study, mostly adjusted across three parameters: tea-to-water ratio, brewing temperature, and brewing duration. Preference level quantification is conducted using different hedonic scales with varying point levels, including 3-point, 5-point, 9-point, and 10-point scales. The quality assessment of tea is measured using various standards, including: Chinese national standard for sensory evaluation of tea, Check All That Apply (CATA), Percentage grading system, unstructured quantitative descriptive analysis, and degree of satisfaction difference. It could be concluded that studies about brewing condition in tea are focused on hot brewing and cold brewing with the optimum value of tea to water ration is 1:50. The sensory evaluation of tea from this different brewing condition is mainly conducted by trained panelists using 10-point hedonic scales as quantitative preference level and Chinese national standard for sensory evaluation of tea as a quality assessment method.